X-ray diffraction study of atomic long-range order of Fe-AI alloy - Repetsky, S.P.; Yaremko, R.O. (Functional Materials, 2005)
Temperature dependence of nonequilibrium values of Fe-AI alloy long-range order parameter has been studied using X-ray diffraction by comparing the integrated intensity of superstructure reflection and fundamental one at small Bragg angles. An additional atomic occupancy of corresponding sublattice sites has been shown to occur as the annealing temperature increases. A partial disordering of the alloy was provided by mechanical polishing with diamond paste; it was manifested itself as a decreasing of superstructure reflection intensities. Such behavior of the long-range order parameter of Fe-50 at. % Al alloy shows that the second order phase transformations are typical of that alloy.